Effect of swim taper on whole muscle and single muscle fiber contractile properties - Trappe, S.; Costill, D.; Thomas, R. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To examine the changes in whole muscle function and single cell contractile properties of Type I and II muscle fibers from the deltoid muscle of highly trained swimmers before and after a 21-d reduction in training volume (taper). Methods: Six college male swimmers (age, 20 +/- 1 yr; height, 187 +/- 2 cm, weight, 79 +/- 3 kg, fat, 7 +/- 1%) who had been, on average, swimming 6200 m.d-1 for 5 months before the taper participated in this investigation. Results: Whole muscle power increased (P < 0.05) 17% and 13% on the swim bench and swim power tests, respectively. Swim times improved by 4% (range: 3.0-4.7%; P < 0.05). There was no change in Type I fiber diameter, whereas Type IIa fibers were 11% larger (P < 0.05) after taper. Peak force (Po) of the Type I fibers was unaffected by the taper but increased (P < 0.05) from 0.63 +/- 0.02 to 0.82 +/- 0.05 mN in the IIa fibers. However, the specific force (Po/CSA) of the IIa fibers was unchanged. Shortening velocity (Vo) was 32% and 67% faster (P < 0.05) in the Type I and IIa fibers, respectively. Although Type I fiber power was unaltered, the IIa fibers increased 2.5-fold from 24.6 +/- 2.8 to 56.2 +/- 3.9 ?N.FL.s-1. When power was normalized for cell size, the power was still elevated twofold. Conclusions: These data suggest that tapering induces alterations in the contractile properties of single muscle fibers. Further, it appears that the Type IIa fibers are more affected than the Type I fibers by the taper. The increased size, strength, velocity, and power of the IIa fibers may be responsible for the improvements in whole muscle strength and power after the taper.